ADSORPTION IN GREEN CHEMISTRY - Estabraq Ali Hameed (European Science Publishing, 2024)
Recently, "green chemistry" has become widely circulated in the scientific community, especially in circles related to the environment and pollution. Green chemistry is a sustainable chemistry that uses the safest and most environmentally friendly chemicals. The adsorption method was used to remove the elements cobalt and cadmium and it was found that this technique depends on the time of contact, adsorbent concentration and pH. The results showed the effectiveness and efficiency of date kernel powder in removing the elements of cobalt and cadmium, followed by corn leaf powder and then ferric chloride. The optimal conditions for achieving the highest removal rate were the use of a concentration of 30 ppm and the best time period of 2 hours and at an acid function ranging between (5-6).
Keywords: Green chemistry, sustainable chemistry, date kernels, corn leaves and percentage removal.